E-COMMERCE IMPLEMENTATIONS FOR RECYCLED PRODUCTS BY SMALL MEDIUM ENTERPRISES - Ratna Marta DHEWI (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2019)
An increasing global awareness on the need for sustainable production and environmental behaviour has encouraged small medium enterprises (SME) to develop products with recycled content. However, how to sustainably marketing the recycled products has also challenged the SMEs. There is a small business managed by orphans in Bogor namely Kelompok Belajar Masyarakat (KBM) Salimah that develop recycled products from plastics and newspaper. Preliminary study has found that there has been a challenge on how to sustain the marketing activities of recycled products in this digital economy. Therefore, it is worth exploring the e-commerce to help such SME to have sustainable business for the recycled products. This research develops a business planning in utilising online shopping, web and social media, establishing customers by email and engaging in online store, furthermore emphasizes on barriers to e-commerce implementation by the SME. The analysis of e-commerce adoption to encourage the benefits for SME and consumers will be presented